Factors affecting employees' intention to quit : a study in a hotel in kuching - Ling, Nyuk King (Universiti Malaysia Sarawak, UNIMAS, 2007)
The aims of this study were to identify employees’ level of intention to quit and factors that affect their level of intention to quit.The factors investigated in this study were age, gender, levels of education, working experience, stressors, support by supervisor, job stress, job satisfaction, locus of control, self esteem, and commitment to the organization. A total of 46 respondents from various departments at Hotel Grand Continental, Kuching were the samples for this study. The study employed a cross -sectional survey research descriptive using questionnaires to collect the required data. Data collected was analyzed descriptively using means and frequencies and inferentially using Independent t-tests, One-way ANOVAs and Pearson Correlation Coefficients. The findings of the study showed that the majority of the employees were occasionally thinking of leaving their present job. There were no significant differences in intention to quit based on demographic factors such as gender, age, and working experience. However, there were significant differences in intention to quit for educational level with Diploma qualifications having higher intention to quit than those with LCE / PMR qualifications. Independent variables such as stressors, support by supervisor, job stress, and job satisfaction showed significant negative relationships with intention to quit. There was no significant relationship for locus of control, self esteem, and commitment to the organzation with intention to quit.